Optimizing the gVERSE RF Pulse Sequence:: An Evaluation of Two Competitive Software Algorithms - Anand, Christopher; Stoyan, Stephen; Terlaky, Tamás (Algorithmic Operations Research)

(untitled) (Preeminent Academic Facets Inc., 2011)
Radio Frequency (RF) pulses cause elevated patient temperatures during Magnetic Resonance Imaging (MRI) procedures. Generalized Variable Rate Selective Excitation (gVERSE) is a co-design method for Radio Frequency (RF) pulse and slice gradient which minimizes Specific Absorption Rate (SAR) (the accepted predictor of patient heating). After developing a rigorous mathematical model, the nonlinear gVERSE optimization problem is solved using two competitive software packages. The gVERSE solutions generated by Sparse Optimal Control Software (SOCS) and AMPL–MINOS produce two separate variations of SAR reducing pulses. The different software solutions are compared using numerical simulations of slice selection. The computational experiments involved with the gVERSE model provided insight towards using different software to solve highly demanding mathematical optimization problems.